Correlation between Mental Health and Professionally Significant Characteristics of the Future Psychologists Personal Maturity - Didik, N. M. (Psychological Prospects Journal, 2012)
Definitions of mental health, its criteria and levels, factors and means which enhance mental health are analyzed in the article. The value of mental health for the profession of practicing psychologist is grounded. Correlation between mental health and personal maturity is analyzed. The research results of mental health and professionally significant characteristics of the future psychologists personal maturity are described. A cross-correlation analysis between them is carried out.